Factors that influences bumiputera participation of SME in Melaka / Nur Adillah Abdul Ghafar (Faculty of Business and Management, 2008)
The purpose of this research is to explore ways to attract and convince investors in Melaka, to identify the challenges occurs to sustain the investors in SME Melaka and to explore the want and need of investors in Melaka Overall result indicates the problems and the challenges occur to sustain the investors in SME Melaka. This finding helps Ministry of Melaka to achieve the mission and vision of Melaka towards 'Melaka Maju 2010'.